2003
DOI: 10.1051/apido:2002047
|View full text |Cite
|
Sign up to set email alerts
|

The detection of Melissococcus pluton in honey bees (Apis mellifera) and their products using a hemi-nested PCR

Abstract: -A hemi-nested polymerase chain reaction (PCR) was further developed for the detection of Melissococcus pluton in adult bees and honey bee products. A chloroform:isoamyl alcohol DNA extraction method was used to provide template from 154 samples of adult bee tissues, honey, pollen, whole larvae and comb cells. All 36 honey bee samples tested from a diseased colony were shown to contain M. pluton and sub-clinical infections were detected in adult bee tissues, larvae and honey (49/98; 50.0%) collected from all 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 12 publications
0
36
0
1
Order By: Relevance
“…Worker bees from the brood nest in apparently healthy colonies can also contain surprisingly high levels of M. plutonius (Roetschi et al, 2008). Adult worker bees act as carriers of the bacterium not only within the colony, but also between colonies and apiaries (Belloy et al, 2007;McKee et al, 2003). More than a third of colonies from apparently healthy apiaries may include adult bees carrying the bacterium, depending on proximity to other apiaries with clinical cases of EFB and almost all colonies within these infected apiaries contain adults that carry the bacterium.…”
Section: Persistence and Transmissionmentioning
confidence: 99%
“…Worker bees from the brood nest in apparently healthy colonies can also contain surprisingly high levels of M. plutonius (Roetschi et al, 2008). Adult worker bees act as carriers of the bacterium not only within the colony, but also between colonies and apiaries (Belloy et al, 2007;McKee et al, 2003). More than a third of colonies from apparently healthy apiaries may include adult bees carrying the bacterium, depending on proximity to other apiaries with clinical cases of EFB and almost all colonies within these infected apiaries contain adults that carry the bacterium.…”
Section: Persistence and Transmissionmentioning
confidence: 99%
“…Although selective media have been used to cultivate M. plutonius (5), the relative complexity of its culture procedure makes it extremely difficult to isolate. Although it can be detected using a PCR method targeting its 16S rRNA sequence (6,8), lack of genome information hinders further development of a rapid and reliable diagnostic method for European foulbrood. The strain selected for sequencing (M. plutonius ATCC 35311) was the type strain of M. plutonius, which was originally deposited at the National Collection of Dairy Organisms by Bailey and Collins (3).…”
mentioning
confidence: 99%
“…Garrido-Bailón et al [1] reported 1.6% prevalance of P. larvae and 0.5% M. plutonius in the honey bees. McKee et al [20] detected M. plutonius 27.5% of these samples. Kılıç et al [17] have identified P. larvae in 7% of the samples by the culture growth method and in 8% of the samples by the PCR method.…”
Section: Discussionmentioning
confidence: 93%
“…Djordjevic et al [19] reported that MP1 and MP2 have been shown to be specific for M. plutonius. The detection of M. plutonius in larvae, in healthy and diseased hives by PCR provides a specific and sensitive method for epidemiological studies in EFB [13,20] . PCR technique is a quick and reliable method for the identification of P. larvae and M. plutonius directly from larvae samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation